Acute colonic pseudo‐obstruction after caesarean section: a review and recommended management algorithm. (26th August 2019) - Hughes, Alice E; Smart, Neil J; Daniels, Ian R
Abstract : Key content: Acute colonic pseudo‐obstruction (ACPO), also known as Ogilvie's syndrome, is a rare but serious complication that may occur after caesarean section. ACPO typically manifests with progressive abdominal distension and discomfort within 48 hours of caesarean section and may be accompanied by electrolyte disturbances and rising levels of C‐reactive protein. If identified early, ACPO can usually be managed conservatively or with neostigmine; even in cases with significant caecal dilatation without evidence of perforation, colonoscopy‐guided decompression can be successful. Worsening abdominal distension, tenderness, or signs of perforation or sepsis imply that laparotomy is necessary. The incidence of laparotomy in reported cases after caesarean section is high, but overall mortality is low; early recognition and appropriate treatment are vital for a good outcome. Learning objectives: To describe the incidence, risk factors and pathophysiology of ACPO following caesarean section. To recognise the clinical presentation of ACPO, including symptoms, signs, results from investigations and potential short‐term and long‐term complications. To understand the indications for conservative, medical, colonoscopic and surgical intervention.